Twenty-first century mast cell stabilizers - WALSH, JOHN (My University, 2013)
Mast cell stabilizing drugs inhibit the release of allergic mediators from mast cells and are used clinically to prevent allergic reactions to common allergens. Despite the relative success of the most commonly prescribed mast cell stabilizer, disodium cromoglycate, in use for the preventative treatment of bronchial asthma, allergic conjunctivitis and vernal keratoconjunctivitis, there still remains an urgent need to design new substances that are less expensive and require less frequent dosing schedules. In this regard, recent developments towards the discovery of the next generation of mast cell stabilizing drugs has included studies on substances isolated from natural sources, biological, newly synthesized compounds and drugs licensed for other indications. The diversity of natural products evaluated range from simple phenols, alkaloids, terpenes to simple amino acids. While in some cases their precise mode of action remains unknown it has nevertheless sparked interest in the development of synthetic derivatives with improved pharmacological properties. Within the purely synthetic class of inhibitors, particular attention has been devoted to the inhibition of important signalling molecules including spleen TK and JAK3. The statin class of cholesterol-lowering drugs as well as nilotinib, a TK inhibitor, are just some examples of clinically used drugs that have been evaluated for their anti-allergic properties. Here, we examine each approach under investigation, summarize the test data generated and offer suggestions for further preclinical evaluation before their therapeutic potential can be realized.
PUBLISHED
Keywords: TK inhibitor; TK inhibitor; Immunology, Inflammation & Infection